THE EFFECT OF THE USE ROLE PLAYING O HAND-WASHING METHOD THROUGH THE REVIEW OF STUDENT KNOWLEDGE: PENGARUH PENGGUNAAN METODE ROLE PLAY PADA CUCI TANGAN YANG BENAR DI TINJAU DARI PENGETAHUAN SISWA - Solehudin Solehudin (Wijaya Husada, 2018)
Handwashing with soap one of the Clean and Healthy Behavior. PHBS is also conducted in schools based on KMK No. 1429 / MENKES / SK / XII / 2006, and became one of the duties of the nurse as an extension worker. The success of counseling with the selection of appropriate methods. The methods used in SMP N 1 Gunung Putri are lecture methods, group discussions, and role play methods. Known data of sick students in 2015/2016, 143 times tifoid become first sequence with incidence 60 times (42%), ISPA 30 times (21%) and skin disease 20 times (14%). By hand washing is expected to reduce disease and can improve student health status. This study analyzes the influence of the use of role play method on hand washing properly viewed from the knowledge of students of class VII SMP N 1 Gunung Putri Bogor in 2016. This type of research is quantitative, quasi experimental design with nonequivalent control group design. By probability sampling technique, that is cluster random sampling. Respondents 50 (25 experiments and 25 controls). Data were obtained through pre and post test with questionnaire and hand washing practice. Statistical analysis used independent t-test, paired t-test, ANNOVA followed by post hoc scheffe. Independent t-test result result is sig.0.610 which means there is no difference between the two classes (equivalent). The result of paired t-test result is sig value in both classes <0.05 which means there is influence of knowledge. The result of post hoc scheffe on the correct knowledge and hand washing produced interaction by looking at significance and mean value ie A2B1 with sig. 0.31 and A2B2 with sig. 0.14 which are both role play classes. Mean A2B2 75.00 which means there is interaction influence so it can be concluded that Ha accepted that there is interaction influence the use of role play method on hand washing is correct in terms of student knowledge. This research is expected to contribute in providing reference in choosing the right method. As well as to wash the right hands become a habit and entrust to the respondents in order to improve the degree of health.